Waves - Crawford, Frank S. (New Delhi, Tata McGraw Hill Publishing Company Limited, 2008)
Features an extensive book covering almost everything concerning wave theory. Detailed explanations supported with illustrations that make the book comprehensive. The approach is highly concrete. Mathematics grows with the book in a very natural way.
Appendices 585-590p.; References 591-592p.; Index 593-600p.
Keywords: Waves; Physics